Shear modulus and damping ratio of a nonplastic silt at large shear strains - Sezer Alper; Karakan Eyyub; Tanrinian Nazar (E3S Web of Conferences, 2019)
Site response analyses and solution of dynamic soil-structure interaction problems need determination of variation of shear modulus and damping ratio with shear strain. Since many studies in literature concern evaluation of behavior of sands and silty sands, a series of cyclic triaxial tests were performed to determine the variation of shear modulus and damping ratio of a nonplastic silt with shear strain. Stress controlled cyclic triaxial tests on silt specimens of initial relative densities ranging among 30%, 50% and 70% were performed. Tests were carried out on identical samples under different CSR levels, and the confining pressure was selected as 100 kPa. Variation of shear modulus and damping ratio of silts with cyclic stress ratio amplitude, relative density and number of cycles were investigated. It was understood that soil relative density and cyclic stress ratio amplitude has a significant influence on shear modulus and damping ratio of silts. It was also observed that, as the cyclic stress ratio amplitude is increased, greater shear modulus and lower damping ratio values were obtained.